Omalizumab effectively protects against early and late allergic responses in asthma after 4 weeks. Issue 12 (28th June 2017) - Trischler, J.; Lieb, A.; Arnold, M.; Schulze, J.; Rosewich, M.; Schubert, R.; Bottoli, I.; Zielen, S.
Abstract: Background: Omalizumab is licensed for therapy in severe allergic asthma with an effect demonstrated after 8 weeks or longer treatment. As new applications for omalizumab demand precise knowledge of the onset of effects, the objective of this study was to determine the time course of the early (EAR) and late allergic reaction (LAR). Materials and Methods: Ten patients (IgE>300 IU/mL and <700 IU/mL) with a significant response to allergen challenge were treated with omalizumab according to the approved dosing table. Bronchial allergen provocations (BAP) were repeated at weeks 1, 2, 4, and 8. Results: EAR was significantly reduced after 4 weeks (ΔFEV1 28% vs 11%; P <.001), eNO (86 vs 53 ppb; P<.05) and basophil activation after 2 weeks (CD63 expression 79% vs 32%, P <.05) and LAR already after 1 week (ΔFEV1 26% vs 13%, P <.05). Conclusion: These results demonstrate the onset of protective effects earlier than previously determined, potentially improving seasonal utilization and combination with immunotherapy.